Studi Literatur : Penerapan Model Pembelajaran Prediction, Observation, and Explanation (POE) pada Pembelajaran Fisika - Puji Purdhiyah; Wulandari, Sri; Wulandari, Mardaya; Annovasho, Jhelang (Charm Sains: Jurnal Pendidikan Fisika, 2022)
This study aims to examine the application of the POE (Prediction, Observation, and Explanation) in learning physics in the last 5 years in terms of advantages and constraints in learning physics in junior high and high school. The process of writing this paper uses a qualitative approach as well as data collection methods for national journal literature studies on POE (Prediction, Observation, and Explanation) in physics learning combined with junior and senior high school physics material. This research activity obtained the results from the application of the POE learning model (Prediction, Observation, and Explanation) which states that it can improve student learning outcomes, improve students' conceptual understanding, improve process skills, improve learning activities and learning outcomes, and improve scientific/process work skills. and learning outcomes. Can be concluded that with the application of the POE learning model as an alternative to physics learning.